Limited Attention and the Residential Energy Efficiency Gap - Palmer, Karen; Walls, Margaret (American Economic Review, 2015)
Inattention may be an important contributor to the energy efficiency gap and may be particularly acute in residential buildings where many different features will determine a home's energy use. Energy audits can provide information on how to reduce energy loss in a home, but the use of audits is rare. We use data from a national survey of 1700 homeowners to study the factors affecting a home owner's choice to have an audit. We create an index of energy inattention for our survey respondents. This index and two additional behavioral factors prove to be important determinants of the audit choice.